Coping behavior of nursing students who experienced verbal abuse in clinical placement / Muhammad Al-Alif Mohd Azman, Nur Amira Razali, Siti Nazirah Kaivaruddin - Mohd Azman, Muhammad Al-Alif; Razali, Nur Amira; Kaivaruddin, Siti Nazirah (2015)
Background: Verbal abuse among nursing student was recognized as a major problem during clinical placement, however coping behavior towards verbal abuse are less been studied by other research. Objective: The purpose of thie study to identify coping behavior of nursing students who experienced verbal abuse during clinical placement. Method: A descriptive study design was carried out whereby a verbal abuse questionnaire was distributed to nursing students. Result:Finding from overall population of 109 nursing students indicated majority of student has been experienced and also witnessed verbal abuse during clinical placement with 79.8% and 78.9% respectively. Patient (56.3%) and clinical instructor (51.0%) has been identified being on top as sources of verbal abuse. The strongest emotional that students experienced verbal abuse has been reported was shame (M=4.02,SD=l.35)9 followed by humiliation (M=3.S2,SD=1.53), frustration (M=3.80,SD=1A1) and sadness/hurt (M=3.76,SD=1.69). There is relationship show that the higher the semester there are more positive coping behavior that been used when they experienced verbal abuse. There is no significant different for negative coping behavior. Conclusion: It can be conclude that the higher the semester the more positive coping behavior nursing students used when they experienced verbal abuse in clinical placement.